Answer:
13825
Step-by-step explanation:
I don’t understand this question can u please clarify it
Answer:
c
Step-by-step explanation:
Answer:
x = -1 and y = -1
Step-by-step explanation:
Solve 3x+3y=−6;−x+y=0
Steps:
I will solve your system by substitution.
−x+y=0;3x+3y=−6
Step: Solve−x+y=0for y:
−x+y+x=0+x(Add x to both sides)
y=x
Step: Substitutexforyin3x+3y=−6:
3x+3y=−6
3x+3x=−6
6x=−6(Simplify both sides of the equation)
6x
6
=
−6
6
(Divide both sides by 6)
x=−1
Step: Substitute−1forxiny=x:
y=x
y=−1
Answer:
x=−1 and y=−1